REPRÉSENTATION DE L’ENFANCE EN RDA DANS TROIS ROMANS GRAPHIQUES DES ANNEES 2000 - Emmanuelle AURENCHE-BEAU (Studia Universitatis Babeş-Bolyai. Philologia, 2017)
A Representation of Childhood in the GDR in Three Graphic Novels of the 2000s. The article deals with three German graphic novels, Grenzgebiete from Claire Lenkova (2009), Such dir was aus, aber beeil dich from Nadia Budde (2009) et Kinderland from Mawil (2014) and studies how the three authors evoke their childhood in the GDR of the 1980ies (autofictional/documentary approach).